Build your own small wind power system - Shea, Kevin; Howard, Brian C. (New York : McGraw-Hill, 2012)
Build Your Own Small Wind Power System focuses on the untapped potential for small wind power closer to home. This hands-on guide shows you how to install a grid-connected, residential-scale, wind power system. You'll get step-by-step details on the'how to' basics of getting your own systems up and running, including how to evaluate your site for wind power potential, getting permits, and financing it--
Includes bibliographical references and index.
Keywords: Wind power; Wind power plants